Harnessing rock climbers for bat conservation: understanding the barriers and benefits for rock climbers to engage in citizen science - Gross, Emily, author; Solomon, Jennifer, advisor; Abrams, Katie, committee member; Davis, Shawn, committee member; Schorr, Rob, committee member (Colorado State University. Libraries, 2024)
Citizen science is a valuable tool for crowdsourcing data, yet it remains underutilized at the nexus of conservation and recreation. The value of citizen science lies in its ability to expand the scope of research by reducing financial burden, increasing data collection over time, and tapping into a diverse pool of skillsets from individuals. Recreators, in particular, can broaden the extent of the project in new ways. Extreme sports participants emerge as a key subgroup of recreators due to their additional specialized skills, knowledge, and daring prowess. This research focuses on one such community of extreme sport participants— rock climbers. Rock climbers are distinguished by their ability to navigate and collect data from vertical environments that remain inaccessible to many biologists. The potential of collaboration is timely, as bats are facing unprecedented threats from white-nose syndrome, wind energy, habitat loss, and climate change. Thus, this research aims to (1) uncover the barriers and motivations for rock climbers to participate in a citizen science initiative called Climbers for Bat Conservation (CBC), (2) explore the relevance of environmental attitudes and knowledge of the organization on climber engagement, and (3) suggest strategies to increase the likelihood of reporting a bat to CBC, utilizing the Community-Based Social Marketing framework. Data for this project was collected using mixed methods, including two sets of semi-structured interviews and a structured survey. Semi-structured interviews were conducted at a rock climbing festival, Rocktoberfest, in Red River Gorge, Kentucky and through the video chat platform, Teams. Results from the semi-structured interviews were used to inform the structured survey. The survey was administered to climbers at Rocktoberfest and to an online database of climbers who reported seeing a bat to CBC. In Chapter 1. I present and discuss the semi-structured interviews, which revealed diverse motivations for participation, including knowledge and experiences with bats, the role of the climbing community, and the complexities of navigating climbing access and conservation. Results of the survey are discussed in Chapter 2., revealing the importance of situational barriers (time, forgetting, and fear of losing access), as well as highlighting the key role that the climbing community plays in influencing behavior. Results also revealed that accurate knowledge of CBC did not have a significant impact on the reporting behavior. It could be that the larger influence on the reporting behavior comes from environmental attitudes, as the results showed that climbers who reported to CBC had a significantly higher proportion of individuals who held pro-environmental attitudes as compared to climbers who had not reported. Both reporting and non-reporting climbers valued the ecological benefits of reporting a bat, highlighting a key topic that can be utilized in future message framing. These findings build upon the growing body of research that demonstrates knowledge alone does not change behavior. This is important for citizen science organizations seeking to utilize rock climbers because many climbers are guided by ecological motivations in tandem with the fear of losing access. My research suggests that acknowledging tradeoffs regarding management of climbing routes and bat conservation while maintaining transparency about how the data will be used will likely aid in recruitment and retention of climber volunteers. Results of this research may aid future citizen science projects in beginning a social marketing campaign for organizations with limited time, budget, and/or staff availability, while shedding light on the motivations of rock climbers to participate in pro-environmental behaviors.
Keywords: bats; collaborative conservation; barriers; social marketing; citizen science